Consideraciones cronológicas sobre la Edad delBronce enLa Mancha. - Fernández Posse, María Dolores; Gilman, Antonio; López González, Luis F.; Martín, Concepción; Orejas, Almudena (Complutum, 1996)
Sin resumen